A multi-criteria proximal bundle-based optimization approach to chick-mash feed formulation - Abayomi, Olalere Olusegun; Ruth, Alara Oluwaseun; Bala, Mohamed Saad; Twibi, Mohamed Farag (Citefactor, 2016)
The development of feed formulation is essentially a problem of optimization which involves selecting the best alternative, starting from a specified set of possibilities. This study is aimed at developing a generic decision supporting system for optimizing the poultry feed production through the application of multi-objective proximal bundle approach, taking into consideration the energy optimization, limiting the amino acid variation and providing a least cost of production. A non-differentiable interactive multi-objective bundle-based optimization method was used in solving this problem. This technique provided a wide range of alternatives choices for the decision maker to formulate an effective and optimum feed that will minimize the costs, achieve more balanced ration, limit the methionine variation for growth, and optimize the metabolized energy based on feed at his/her disposal. The algorithm of this method is based on the objective functions classification. According to this classification, a new (multi-objective) optimization problem was formed and solved by a Multi-objective Proximal Bundle method. The method in turn generated different alternative formulations from which the decision maker arrived at the final decision